Temporal processing in the auditory brainstem response by full-term 6-week- and 9-month-old infants - Mai, Xiaoqin (Sci Rep, 2015)
Early auditory temporal processing abilities are important for language acquisition and for later reading abilities. In the present study, auditory brainstem responses (ABRs) were recorded in a forward-masking paradigm in healthy, full-term infants aged 6 weeks (n = 111) and 9 months (n = 62). Our purpose was to establish normative values of forward-masking ABRs and investigate the development of auditory temporal processing in infants at these ages. Infants were presented with pairs of stimuli (an initial “masker” followed by a “probe”) separated by different time intervals (8, 16, and 64 ms). Results showed that as masker-probe intervals became longer and as infants got older, Wave V latency to the probe shortened. The greatest improvements in Wave V latencies from 6 weeks to 9 months of age were observed in the 64-ms masker-probe interval, suggesting that central auditory nervous system related to the temporal processing at this interval might undergo rapid development during the first year of life.